Aging mechanism and surface properties of Silica fluoropolymer coating and its application. (25th November 2020) - Huang, Hongpu; Guo, Hong; Qu, Jia; Feng, Yefeng
Abstract: The hydrothermal aging cycles experiment was carried out on synthetic Silica fluoropolymer coating (SiO2 -FP). The hydrothermal aging mechanism, surface properties and protective efficacy on sandstones was studied. For comparison, the same study was conducted for commercial protective material acrylic resin Paraloid B72 (PB72). The hydrothermal aging mechanism was studied by Fourier infrared spectroscopy attenuated total reflection technique (ATR-FTIR) and x-ray photoelectron spectroscopy (XPS) technology. The surface properties were characterized by field emission scanning electron microscope (SEM), the CR-400 color difference meter, static contact angle and GMT6503 Electronic universal Tensile machine. The capillary water absorption, water absorption by complete immersion (CI) and water vapor permeability were measured to evaluate the protective efficacy on sandstones after treatment. The results of ATR-FTIR and XPS indicated that part of the ester groups in PB72 was hydrolysed and the chemical structure of SiO2 -FP was not changed but only microphase separation occurred after 360 h of aging. After 360 h of aging, the PB72 film had obvious change and the SiO2 -FP film only shown a minor change; the color change of PB72 film was very obvious and the color change of SiO2 -FP film was within the acceptable range; the PB72 film changed from hydrophobic to hydrophilic and the SiO2 -FP film still retained high hydrophobicity (119.3°); the SiO2 -FP had a higher adhesive strength than PB72 at the end of aging. Compared with PB72, the SiO2 -FP can obviously reduce the capillary water absorption and had a higher protective efficiency (97.25%), much lower soakage capacity (0.60%), higher water vapor permeability (267.0 ± 2) and less influence on the water vapor permeability. All the results demonstrated that the SiO2 -FP has much better anti-aging ability and longer durability under hydrothermal condition. The SiO2 -FP can provide adequate protection for sandstones. The SiO2 -FP can be used as a suitable protective coating on sandstones.